Real-Time DVB-MHP Interactive Data Transcoding to Blu-Ray. (9th November 2008) - Infante, Sergio; Nasiopoulos, Panos
Abstract : Digital TV systems are being deployed worldwide, and interactive applications are being offered as part of the services. The unparalleled success of DVD technology has motivated the development of interactive services for broadcast TV, with DVB-MHP being the most widely used open standard in the world. Despite the similarities between DVB-MHP-based interactive TV and the new Blu-ray format, there still exist substantial differences that make the two systems incompatible. In this paper, we analyze the differences in the DVB-MHP and Blu-ray interactive formats and propose a transcoding scheme to convert live broadcast interactive TV to a Blu-ray compatible format.